2012
DOI: 10.1093/pasj/64.6.135
|View full text |Cite
|
Sign up to set email alerts
|

Substellar Companions to Seven Evolved Intermediate-Mass Stars

Abstract: We report on the detections of substellar companions orbiting around seven evolved intermediate-mass stars from precise Doppler measurements at Okayama Astrophysical Observatory. $o$ UMa (G4 II-III) is a giant with a mass of 3.1 $M_{\odot}$ , and hosts a planet with a minimum mass of $m_2$ sin $i$$=$ 4.1 $M_{\rm J}$ in an orbit with a period $P$$=$ 1630 d and an eccentricity $e$$=$ 0.13. This is the first planet candidate ($\lt $ 13 $M_{\rm J}$ ) ever discovered around a star more massive than 3 $M_{\odot}$ . … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 50 publications
4
53
1
Order By: Relevance
“…Orbital values for the companions to Pollux and ν Oph are taken from our data, since it is the most extensive RV data set for these stars, with the best available orbital fits. There are, however, other published values (Hatzes et al 2006;Sato et al 2012). In particular, the alternate published value for the companion to Pollux lists an eccentricity of 0.02 ± 0.03, as opposed to our current best fit value of 0.05 ± 0.01.…”
Section: Eccentricitycontrasting
confidence: 89%
“…Orbital values for the companions to Pollux and ν Oph are taken from our data, since it is the most extensive RV data set for these stars, with the best available orbital fits. There are, however, other published values (Hatzes et al 2006;Sato et al 2012). In particular, the alternate published value for the companion to Pollux lists an eccentricity of 0.02 ± 0.03, as opposed to our current best fit value of 0.05 ± 0.01.…”
Section: Eccentricitycontrasting
confidence: 89%
“…Based on our Lick data, two brown dwarf companions were first discovered by Quirrenbach et al (2011) and later confirmed by Sato et al (2012). The Keplerian nature of the optical velocity data was generally accepted, since other phenomena intrinsic to the star are very unlikely to be responsible for the Doppler signal.…”
Section: Substellar Companionsmentioning
confidence: 73%
“…omi CrB: Sato et al (2012) reported a 1.5 M jup giant planet orbiting around omi CrB, assuming a stellar mass of 2.13 M . With our mass determination of 1.07 M we put the planet at a subJupiter mass class with only 0.65 M jup .…”
Section: Impact Of Planetary Massesmentioning
confidence: 99%